Global Trade Policy : - Smith, Pamela J (Wiley, 2013)
Global Trade Policy offers accessible coverage of the key questions in trade and policy; it charts the changing policy landscape and evolving institutional arrangements for trade policies, examines trade theory, and provides students with an economic framework to better understand the current issues in national and international trade policy.